Chitosan-tripolyphosphate nanoparticles encapsulated rutin targeting bacterial growth inhibition and its cytotoxicity on PANC-1 pancreatic adenocarcinoma cell - K. T. Ramya Devi, Shalini James Paulraj, Yashesh Shah, Santhosh Raja Kumar, Priyatharcini Kejamurthy (Journal of Applied Pharmaceutical Science, 2023)
Nano-carrier systems are highly explored for the slow release of a drug. Chitosan (CS), a polymer, has more applications in nano-drug carrier systems. To explore these applications, currently, we synthesized CS nanoparticles (CS-NPs), and it was allowed to encapsulate free Rutin (RUT) and it resulting in CS-NPs/RUT. Further, it was characterized, and the size of CS-NPs was found to be 79 nm, and upon encapsulating RUT, the particle size was increased to 173 nm, which resulted in CS-NPs/RUT. The entrapment of RUT with CS-NPs was found to be -85%. MTT-based cytotoxicity assay represented the non-lethal nature of CS-NPs/RUT toward normal osteoblast cells, C3H10T1/2 clone8, and showed cytotoxicity against pancreatic adenocarcinoma cells, PANC-1. Furthermore, we extended the study to analyze bacterial growth inhibition and incorporation by CS-encapsulated RUT. It was performed through flow cytometry in different concentrations of 100, 200, and 300 μg/ml of treatments in Escherichia coli. The bacterial inhibition and incorporation of bacteria were significantly higher in CS-NPs/RUT compared with RUT. Hence, the experiments depicted the superiority of CS-NPs/RUT over free RUT that suggested, CS encapsulation as an efficient system for delivering RUT for bacterial growth inhibition and also anti-cancer cell proliferation.